Results from a 9‐year Intensive Safety Surveillance Scheme (IS3) in miglustat (Zavesca®)‐treated patients. (5th February 2015) - Brand, Monika; Muller, Audrey; Alsop, Jonathan; van Schaik, Ivo N.; Bembi, Bruno; Hughes, Derralynn
Abstract: Background: Following approval in the EU in 2002 and the USA in 2003, an Intensive Safety Surveillance Scheme (IS 3 ) was initiated to educate prescribers on the appropriate use of miglustat for the treatment of type I Gaucher disease (GD1), and to actively solicit safety‐relevant information. This report summarises data from all patients enrolled in IS 3 between its initiation in 2003 and its closure in October 2012. Methods: The IS 3 was a prospective observational drug registry with a secure internet‐based data capture system. All patients receiving miglustat at participating sites received standard medical care according to routine medical practice. Data on patient and disease characteristics were collected at patient enrolment, subsequent follow‐up visits and treatment discontinuation (if applicable). Data were summarised using descriptive statistics. Results: During the 9 years of IS 3, 407 patients were enrolled at 111 sites across 15 European countries. Approximately half ( n  = 202) had GD1, and half had other diseases (mainly Niemann–Pick disease type C (NP‐C), for which miglustat was approved in Europe in 2009). In total, 368 patients had data from at least one follow‐up visit, 192 of whom had GD1. IS 3 provided data from 798 patient‐years exposure to miglustat. Safety‐relevant data were consistent with earlier published 5‐year findings from IS 3, the safety profile reported for miglustat in GD1 clinical trials and other published information on GD1 manifestations. Conclusions: Overall, the results of this long‐term safety surveillance programme were in line with the well‐known, documented safety profile of miglustat. Copyright © 2015 John Wiley & Sons, Ltd.